FAM5C contributes to aggressive periodontitis. - Flavia M Carvalho; Eduardo M B Tinoco; Kathleen Deeley; Poliana M Duarte; Marcelo Faveri; Marcelo R Marques; Adriana C Mendonça; Xiaojing Wang; Karen Cuenco; Renato Menezes; Gustavo P Garlet; Alexandre R Vieira (PLoS ONE, 2010)
Aggressive periodontitis is characterized by a rapid and severe periodontal destruction in young systemically healthy subjects. A greater prevalence is reported in Africans and African descendent groups than in Caucasians and Hispanics. We first fine mapped the interval 1q24.2 to 1q31.3 suggested as containing an aggressive periodontitis locus. Three hundred and eighty-nine subjects from 55 pedigrees were studied. Saliva samples were collected from all subjects, and DNA was extracted. Twenty-one single nucleotide polymorphisms were selected and analyzed by standard polymerase chain reaction using TaqMan chemistry. Non-parametric linkage and transmission distortion analyses were performed. Although linkage results were negative, statistically significant association between two markers, rs1935881 and rs1342913, in the FAM5C gene and aggressive periodontitis (p = 0.03) was found. Haplotype analysis showed an association between aggressive periodontitis and the haplotype A-G (rs1935881-rs1342913; p = 0.009). Sequence analysis of FAM5C coding regions did not disclose any mutations, but two variants in conserved intronic regions of FAM5C, rs57694932 and rs10494634, were found. However, these two variants are not associated with aggressive periodontitis. Secondly, we investigated the pattern of FAM5C expression in aggressive periodontitis lesions and its possible correlations with inflammatory/immunological factors and pathogens commonly associated with periodontal diseases. FAM5C mRNA expression was significantly higher in diseased versus healthy sites, and was found to be correlated to the IL-1beta, IL-17A, IL-4 and RANKL mRNA levels. No correlations were found between FAM5C levels and the presence and load of red complex periodontopathogens or Aggregatibacter actinomycetemcomitans. This study provides evidence that FAM5C contributes to aggressive periodontitis.